2022
DOI: 10.3390/ma15103685
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Application of Natural Clinoptilolite-Rich Zeolite as Support for Bacterial Community Formation for Wastewater Treatment

Abstract: The aim of this study was to investigate the use of natural zeolite as support for microbial community formation during wastewater treatment. Scanning electron microscopy (SEM), thermal decomposition and differential thermogravimetric curves (TGA/DGT) techniques were used for the physicochemical and structural characterization of zeolites. The chemical characterization of wastewater was performed before and after treatment, after 30 days of using stationary zeolite as support. The chemical composition of waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In addition, after alginate coating, calcium deposition increased in both 7 and 14 days. Similarly, various studies [68][69][70][71][72][73][74][75][76][77][78][79][80] reported that alginate coating increased calcium deposition and new bone formation. For example, Jang et al [69] demonstrated the great calcium deposition results on the PCL scaffold with alginate coating.…”
Section: In Vitro Cytocompatibility Of Scaffoldsmentioning
confidence: 91%
“…In addition, after alginate coating, calcium deposition increased in both 7 and 14 days. Similarly, various studies [68][69][70][71][72][73][74][75][76][77][78][79][80] reported that alginate coating increased calcium deposition and new bone formation. For example, Jang et al [69] demonstrated the great calcium deposition results on the PCL scaffold with alginate coating.…”
Section: In Vitro Cytocompatibility Of Scaffoldsmentioning
confidence: 91%
“…This was probably due to a higher partition coefficient for zinc than for cadmium and a stronger binding of the zeolite to zinc. In contrast, Senila et al [ 180 ] showed that clinoptilolite, in addition to being an adsorbent of contaminants, can also act as a carrier for biofilm formation and microbial growth involved in biological wastewater treatment, which has a beneficial effect on the overall process. The usefulness of silver-modified clinoptilolite in immobilizing Cr(VI) ions from model wastewater was demonstrated by Panayotova [ 181 ].…”
Section: Applications Of Zeolitesmentioning
confidence: 99%
“…Detoxifying Effects of Zeolite-Ammonium, Nitrates, Nitrites, Mycotoxins, Pesticides, Synthetic Neurotoxins, and Radionuclides Diets rich in proteins and with reduced carbohydrate content modify the colonic microbiome, favoring a potentially pathogenic and pro-inflammatory microbiota profile, decreasing short-chain fatty acid production, and increasing ammonia and hydrogen sulphide concentrations, the latter, reflecting excessive protein fermentation, being implicated in the pathogenesis of irritable bowel syndrome, ulcerative colitis, and colorectal carcinogenesis as well [92]. Zeolite has a proven very high affinity toward ammonium (the selectivity of ion exchange on natural clinoptilolite has been reported in an order of K + > NH 4 + > Na + > Ca 2+ > Mg 2+ (e.g., [93,94])) and has long been used to efficiently remove ammonium from fresh and waste water [55,[95][96][97][98] and also shows favorable effects in humans when used as a supplement in the protein-rich diet of endurance-trained individuals [91]. Except for ammonium (NH 4 + ), zeolite has shown high removal efficiency for nitrates (NO 3 − ) and nitrites (NO 2 − ) as well [55,99].…”
Section: Detoxifying Effects Of Zeolitementioning
confidence: 99%